The Business Judgment Rule in a Progressive Legal Perspective: Essence and Implications in Indonesia: Business Judgment Rule dalam Perspektif Hukum Progresif: Esensi dan Implikasinya di Indonesia - Shafira, Wilda; Izzah, Ananda Elena Nurul; Pamella, Primanadya Dian; Dzakirah, Nabila Ghina (Rechtsidee, 2022)
The business judgment rule is a concept of business law to provide protection for the directors and commissioners of the company regarding liability due to decisions or policies that harm the company. This concept is important to realize creative and innovative directors in carrying out business practices. This study aims to explore the progressive legal aspects of the business judgment rule concept. This research is a normative legal research oriented to the study of the concept of business judgment rule and the theoretical study of progressive law. The primary legal materials in this study include: the 1945 Constitution of the Republic of Indonesia, the PT Law, and the POJK on the Board of Directors and Board of Commissioners of Issuers or Public Companies. Secondary legal materials include: the results of studies and research that discusses the concept of business judgment rule and progressive law. Non-legal materials include legal dictionaries. The results of the study confirm that the essence of the concept of business judgment rule is to optimize the effectiveness and efficiency of the company. This includes providing guarantees for protection and legal certainty for directors and commissioners regarding liability for company losses that can be excluded through the concept of a business judgment rule. The implications of the business judgment rule in the perspective of progressive law can be done by revising Article 97 paragraph (5) of the Limited Liability Company Law to guarantee the limits of the business judgment rule more specifically so as to ensure legal certainty, prioritizing human values ​​in progressive law as guiding values ​​in reading the formulation of Article 97 paragraph (5) PT Law, as well as the role of judges in court through their decisions to develop the concept of a business judgment rule in practice.